From Comrades to Bodhisattvas Moral Dimensions of Lay Buddhist Practice in Contemporary China - Fisher, Gareth (Topics in Contemporary Buddhism, 2014)
From Comrades to Bodhisattvas is the first book-length study of Han Chinese Buddhism in post-Mao China. Using an ethnographic approach supported by over a decade of field research, it provides an intimate portrait of lay Buddhist practitioners in Beijing who have recently embraced a religion that they were once socialized to see as harmful superstition. The book focuses on the lively discourses and debates that take place among these new practitioners in an unused courtyard of a Beijing temple. In this non-monastic space, which shrinks each year as the temple authorities expand their commercial activities, laypersons gather to distribute and exchange Buddhist-themed media, listen to the fiery sermons of charismatic preachers, and seek solutions to personal moral crises.